Experiences of how services supporting women with perinatal mental health difficulties work with their families: a qualitative study in England. Issue 7 (24th July 2019) - Lever Taylor, Billie; Billings, Jo; Morant, Nicola; Bick, Debra; Johnson, Sonia
Abstract : Objectives: Partners and wider family members play a vital role in relation to women's perinatal mental health. Clinical guidelines in the UK and internationally recommend that services supporting women with perinatal mental health difficulties involve and support their families too. However, little is known about family members' needs and experiences, or whether they feel included by mental health services. This study set out to explore this. Methods: This research formed part of a wider study exploring experiences of perinatal mental health care in England. The broader study included semi-structured interviews with 52 women across England who received treatment for a perinatal mental health difficulty, and 32 family members identified by the women as offering them some support. Data from these 84 interviews relating to how services work with partners and families were extracted and analysed thematically. Results: Analysis identified three overarching themes: (1) the centrality of women's families to their perinatal mental health/access to support, (2) experiences of partners and families being excluded by services and (3) ambivalence among women and their families about increasing family involvement/support. We found that partners and families appear to have an important influence on women's perinatal mental health, access to care and interactions with services, but that services tend to focus on individual women (and babies) with little regard for their wider family context. The complexity of involving and supporting partners and families, coupled with anxiety about this among women and their families, reinforces the tendency to marginalise them. Conclusion: Involving women's families and providing the support they need is challenging, but important. Experiences of women and their families of services treating perinatal mental health difficulties suggests greater focus is needed on overcoming barriers to family inclusion and on challenging underlying gender roles and expectations, rather than allowing these to shape and guide practice.